Militarization of the anthropocene through solar geoengineering applications - Bekim Nuhija; Stefani Stojchevska (University American College Skopje, 2020)
While currently living in the geological epoch of the Anthropocene, mankind is consequently fighting against climate change and other hazardous environmental issues. Although solar geoengineering has been proposed as a promising solution, the universal fear regarding its military misuse is still prominent and widely existent. It is believed that this fear could lay the foundation for the concept of a militarized Anthropocene - the manifestation of preset temporal aspects of humanity's destructive influence regarding climate change for military use. Contrastingly enough, there are a multitude of factors which manifest unrealistic expectations in relation to this concept. While emphasizing the importance of the military as the most suitable governmental institution for developing and utilizing solar geoengineering techniques, this paper aims to address such presumptions through anthropological, ethical, legislative, as well as argumentative approaches. Misleading public opinion, particularly, as a biased perception fails to recognize that military-aimed solar geoengineering methods does not represent a risk by itself, but rather the interference between the belligerent nations and should be concerned as national security. Moreover, the emergence of the slippery slope argument manifested by global psychology and international awareness causes military-related disadvantages concerning the utilization of solar geoengineering as a method of weather warfare. The concept of a militarized Anthropocene, although seemingly controversial, would only enhance the benefits of military-conducted solar geoengineering methods that will be felt by humanity for centuries to come.
Keywords: 330; solar geoengineering; military; ethics; policy; anthropocene; weather warfare